Ideal convergence and ideal Cauchy sequences in intuitionistic fuzzy metric spaces - Or, Aykut; Karabacak, Gökay (Mathematica Moravica, 2023)
The present study introduces the concepts of ideal convergence (I-convergence), ideal Cauchy (I-Cauchy) sequences, I *-convergence, and I *-Cauchy sequences in intuitionistic fuzzy metric spaces. It defines I-limit and I-cluster points as a sequence in these spaces. Afterward, it examines some of their basic properties. Lastly, the paper discusses whether phenomena should be further investigated.